Humic Substances Effect and Climatic Tensions on the Growth and Essential Oil Quality of the Cultivated Aloysia. triphylla (Iran) - Sardashti , A.R.; Assadi-Khanoki , A. (Jordan Journal of Agricultural Sciences, 2021)
Aloysia. triphylla (L, H, er.) Britton (Family Verbenaceae) is studded for nutritional and pharmacological purposes. Soil factors and climatic tensions affect the growth of the herbs. A. triphylla plants were planted in the University greenhouse (Zahedan) in March. Humic substances solutions were sprinkled onto the soil surrounding the root of the plant. This way of planting simultaneously was repeated in the Zahedan outskirts and Zarand area. In late June, the leaves of planted samples were collected and prepared for senescing through the hydrodistillation method. After collecting leaves and be sprinkled with humic substances solution onto the soil surrounding root of the same plant, the leaves were picked up again in late September for oil extraction. Oil yields (w/w%) of the greenhouse's June samples were 0.45 and 0.48 for the blank and humic samples respectively. By analyzing oils, using GC & GC-MS techniques, 47 and 46 compounds were identified from the blank sample and humic sample oils, constituting 93.21% and 91.58% respectively. The higher percent of which: limonene, 1, 8-cineole, Z-citral, E-citral, bicylogermacrene, trans-caryophyllene, panthenol compounds. Oxygenated terpenoids percentage in the humic sample oils varies between 43.70 and 60.16 of which 43.70 belongs to the oil of Zarand September humic sample (Sapropel) and 60.16 to the oil of the greenhouse's June humic sample (Sapropel). Oxygenated terpenoid compounds in September samples were less than those of June samples. These changes result from humic substances and climatic tensions. As a result, the flowering period is shortened and the oil quality has been optimized.